Long-whisker type TiB phase introduced by micron-sized precursors and its prominent strengthening effect in titanium matrix composites - Li, Qiang (2022)
We developed a new strategy to obtain long whisker (LW) TiB phase (aspect ratio as high as ∼150) using micron-sized AlB2 in a series of TiB/Ti(Al) composites. While three types of TiB phases were present in the composites, microhardness and compression results show that LW-type TiB enhances yield strength dramatically.